ACUTE CAROTID STENT THROMBOSIS – A RARE CLINICAL ENTITY? - Coelho, Andreia (2019)
Introduction: Acute carotid stent thrombosis (ACST), defined according to the Academic Research Consortium as occurring in the first 24 hours after the procedure, is described as an exceedingly rare complication of CAS but it can lead to catastrophic neurologic consequences. The European Society for Vascular Surgery updated guidelines state thrombolysis and intravenous abciximab may be effective, but provide no specific recommendations. Given the lack of data concerning the optimal management, the purpose of this review was to evaluate the current literature and report on ACST aetiology and management strategies. Methods: Literature review was performed in the MEDLINE database. Results: No data on ACST is evident in large randomized controlled trials. ACST incidence rate ranges from 0.5-0.8%, reaching as high as 33% in acute-setting.   Considering aetiology, it can be subdivided into 2 main groups: systemic causes and technical complications. In the first antiplatelet non-compliance/resistance were the most reported while in the latter carotid artery dissection and plaque protrusion were the most common causes. Also, dual layer stents were associated with greater risk for ACST There are three main approaches for ACST: pharmacologic, endovascular and surgical. Pharmacologic management included anticoagulation, thrombolysis and facilitated thrombolysis. A role for thrombolysis and facilitated thrombolysis is still to be determined. Endovascular treatment was the most common approach to intraprocedural ACST: mechanical thrombectomy with or without concomitant facilitated thrombolysis. Surgical options included carotid endarterectomy with stent explantation which was a bail-out after failed endovascular treatment with excellent recanalization rates. In asymptomatic ACST conservative management with anticoagulation was unanimous. Discussion: As a conclusion, ACST is probably an underestimated clinical entity associated with multiple risk factors. Decision on the best approach depends if ACST occurs intraprocedural or afterwards, on the development of neurologic status deterioration and on centre´s experience. Additional studies must be undertaken to better define optimal management.